Uji Kinerja Saluran Tersier pada Daerah Layanan Jaringan Irigasi Tersier dengan Luas 25 Ha - Julianto, Julianto; Ridwan, Ridwan; Suharyatun, Siti; Amin, Muhammad (Jurnal Agricultural Biosystem Engineering, 2022)
The performance of the irrigation network can be seen from several aspects such as the condition of the door and the suitability of the discharge coming out of the measuring instrument or door opening that is operated. This is used as information and input in the management of irrigation networks so that the distribution of water can be precise and even as well as a benchmark in evaluating water distribution. The performance of the tertiary irrigation network is measured based on six parameters. This parameter will determine whether or not there is an error in the management of the irrigation network. Good irrigation network performance will produce water discharge in accordance with irrigation water needs in each tertiary plot. The performance of the tertiary irrigation network on the Crump De Gruyter type has a very good performance. The level of efficiency of water use in the downstream area is higher than in the middle and upstream areas. Water distribution was 1.07 l/sec/ha during treatment, 0.82 l/sec/ha during plant growth and 0.4 l/sec/ha plant ripening.